Bioactive calcium phosphate cement with excellent injectability, mineralization capacity and drug-delivery properties for dental biomimetic reconstruction and minimum intervention therapy. Issue 33 (15th March 2016) - Sa, Yue; Gao, Yixue; Wang, Man; Wang, Tianfeng; Feng, Xiaowei; Wang, Zhejun; Wang, Yining; Jiang, Tao
Abstract : CPC could be used as a promising biomaterial to reconstruct the breached enamel on exposed dentin through a biomimetic and minimally invasive way. Abstract : When the enamel layer is breached due to external physical and chemical reasons, the underlying dentin is exposed to a wet and bacteria-laden oral environment. Accordingly, some diseases related to exposed dentin, such as dentin hypersensitivity and bacterial invasion, usually occur and affect patients' day-to-day lives. The aim of this study was to evaluate the effectiveness of injectable calcium phosphate cement (CPC) on occluding dentinal tubules and antibacterial properties when loaded with chlorhexidine (CHX) under a simulated oral environment, which was believed to be beneficial for dental biomimetic reconstruction and minimum intervention therapy. The particle size, surface morphology and composition of CPC were characterized using scanning electron microscopy (SEM) and X-ray diffraction (XRD). The apatite formation ability, occluding effects, drug delivery and antibacterial properties of CPC and CHX-loaded CPC were further investigated using non-destructive attenuated total reflection infrared (ATR-IR) spectroscopy, Raman spectroscopy, SEM observation, permeability test, UV analysis and a disk-diffusion method. The results showed that both CPC and CHX-loaded CPC could continually form enamel-like apatite layers on the exposed dentin surface. After facing an acidic environment, the apatite layer still effectively occluded the dentinal tubules. Furthermore, CHX loaded CPC showed a sustained release of CHX over a timeframe of a week and revealed significant antibacterial effect compared to the blank control without CHX. Therefore, the results suggest that due to the unique self-setting ability, injectability, apatite-mineralization capacity and similar composition to a tooth, CPC could be used as a promising biomaterial to reconstruct the breached enamel on exposed dentin through a biomimetic and minimally invasive way. Moreover, due to the excellent drug-delivery property, CPC could easily carry antibiotics to inhibit the bacteria causing further pulp infection.